2014
DOI: 10.1007/s11033-014-3748-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the interleukin-1β-511 C/T gene polymorphism on the risk of gastric cancer in the context of the relationship between race and H. pylori infection: a meta-analysis of 20,000 subjects

Abstract: The interleukin (IL)-1β-511 C/T polymorphism has been shown to be functional and to contribute to the risk of gastric cancer. However, the relationship between the IL-1β-511 C/T polymorphism and gastric carcinogenesis remains inconclusive. A systematical electronic search was conducted of the MEDLINE, EMBASE, and CENTRAL databases. A random and a fixed effects model were exploited to estimate summary odds ratios and 95 % confidence intervals. Subgroup and sensitivity analyses were carried out with respect to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 59 publications
1
12
0
1
Order By: Relevance
“…Our study did not find significant association between polymorphisms in IL12B or IL10 genes with GC risk. Our results support the previous data to other populations, which analyzed associations between SNPs in genes regulating the inflammatory response and GC[30-32,34]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study did not find significant association between polymorphisms in IL12B or IL10 genes with GC risk. Our results support the previous data to other populations, which analyzed associations between SNPs in genes regulating the inflammatory response and GC[30-32,34]. …”
Section: Discussionsupporting
confidence: 92%
“…To date, different gene polymorphism related to inflammatory pathways have been evaluated, with IL-1B and IL-1RN being the most widely studied ones[18,30-34]. Computational analysis tools that we used in our study suggested two genes polymorphisms - IL12B (rs1368439) and IL10 (rs3024498) - situated in inflammatory pathways, that might be the involved in miRNA-target gene interaction[16].…”
Section: Discussionmentioning
confidence: 99%
“…pylori infection reinforces the relation between IL-1β-511 T allele with susceptibility to gastric cancer[OR = 2.04, 95%CI = 1.15–3.62 for recessive model], which means H . pylori infection as a risk factor might have synergistic effect with IL-1B-511T allele the development of GC[28]. However, it exists a high Heterogeneity[P<0.0001, I 2 = 84%].…”
Section: Discussionmentioning
confidence: 99%
“…Caleman Neto A et al [24] revealed that it was IL-8-251T/A polymorphism associated with H . pylori infection instead of IL-1B-511 C/T polymorphisms, but Park MJ [28] suggested that H . pylori infection might increase the association between IL-1B-511C/T and stomach carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…A very recent meta-analysis reported similar correlation where the T/T genotype of IL-1β-31 increased GC risk only in individuals with H. pylori infection (table 1) [51]. A meta-analysis of IL-1β-551C/T included 45 studies and showed that the T/T genotype could evaluate GC risk in subjects with H. pylori infection (OR: 1.70; 95% CI: 1.03-2.80; I 2 = 85%) (table 1) [52]. However, a meta-analysis on the IL1-RN VNTR polymorphism and GC risk showed that the IL1-RN*2 allele was associated with higher GC risk but independent of H. pylori infection (table 1) [53].…”
mentioning
confidence: 99%